Prarancangan Pabrik Metil Laktat Dari Asam Laktat Dan Metanol Kapasitas 20.000 Ton/Tahun - Prakoso, Titus Dwi, Eni Budiyati, S.T., M.Eng, Hamid Abdillah, S.T., M.T (2016)
Methyl lactate with formula CH¬3CHOHCOOCH3 ester derivative is an organic compound that is used as an organic solvent (in the manufacture of cellulose acetate, cellulose nitrate, cellulose asetopropinat, and ethyl cellulose) and an intermediate chemical compound (used in the plastics industry, synthetic resins and paints). Methyl lactate needs in Indonesia are imported from the United States, China and Taiwan. This is due to the absence of methyl lactate factory in Indonesia. Factory methyl lactate with a capacity of 20,000 tons / year is planned to be in Bontang, East Kalimantan, with a land area of 30,000 m2 and the number of employees 172 people. The raw material used is a lactic acid imported from China and methanol imported from PT. Kaltim Methanol Industry in East Kalimantan. The process of making methyl lactate using esterification process with reactant mole ratio of 4: 1 (methanol: lactic acid) in Continuous Stirred Tank Reactor (CSTR) for 60 minutes. This process takes place is irreversible, exothermic, non-adiabatic at a temperature of 100 ° C with a pressure of 2.4 atm. Methanol feedstock requirements of 5519.510 tonnes / year and lactic acid amounted 16764.453 tons / year. Methyl lactate products by 20,000 tons / year. At the unit takes water utilities 30618.652 m3 / year, amounting to 765,162.3 kW of electricity. Factory methyl lactate were established requiring a fixed capital of Rp392.224.488.140,21 and working capital of Rp 131,602,683,941.38. Based on economic analysis showed profits before tax of Rp 116,469,144,156.74 per year and after tax of Rp 81,528,400,909.72 per year. Percent of Return On Investment (ROI) before tax amounted to 29.69%, after tax amounted to 20.79%. Pay Out Time (POT) before taxes of 2.52 years, 3.25 years after tax. Break Even Point (BEP) amounted to 47.2% and Shut Down Point (SDP) amounted to 24.18%. Internal Rate of Return based on discounted cash flow (i)of 37.8% According to the feasibility analysis above it can be concluded that the plant is profitable and feasible to set.